PRODUCTION OF BIODEGRADABLE PLASTICS AS SUBSTITUTE FOR CONVECTIONAL PLASTICS IN NIGERIA - Qasim, Musa; Oyegoke, Toyese; Omale, Sunday (FUDMA JOURNAL OF SCIENCES, 2022)
The world is moving towards the 2050 net-zero emissions goal and tackling the ever-growing environmental and sustainability crisis by implementing the European Green Deal. The move towards a more sustainable society in Nigeria is success with the production, use, and disposal of plastic in Nigeria. Emissions generated by plastic production, and unlimited-growing of plastic waste has a huge negative impact on the living organisms because of the large accumulation in the landfills and aquatic environment. Adoption of bioplastics, which is under assessment, is one way to decouple Nigeria from the use of fossil resources, and to mitigate specific environmental risks related to plastic waste. In this work, we aim at reviewing the viability of bioplastics production in Nigeria, work done and yet to be done for effective production and commercialization. We also discuss some of the merits and challenges that can be currently identified with the adoption of these processes in Nigeria.